The importance of textile strings in a traffic violation (Academic Journal of Internal Affairs, 2016)
Through the analysis of a particular Hungarian case, the author provides an overview of the complexity of assessing conditional probability in forensic science within the legal procedure.
Keywords: conditional probability; forensic science; case study